Maintenance, reserve and compensation: the cognitive neuroscience of healthy ageing. Issue 11 (November 2018) - Cabeza, Roberto; Albert, Marilyn; Belleville, Sylvie; Craik, Fergus; Duarte, Audrey; Grady, Cheryl; Lindenberger, Ulman; Nyberg, Lars; Park, Denise; Reuter-Lorenz, Patricia; Rugg, Michael; Steffener, Jason; et al.
Abstract Cognitive ageing research examines the cognitive abilities that are preserved and/or those that decline with advanced age. There is great individual variability in cognitive ageing trajectories. Some older adults show little decline in cognitive ability compared with young adults and are thus termed 'optimally ageing'. By contrast, others exhibit substantial cognitive decline and may develop dementia. Human neuroimaging research has led to a number of important advances in our understanding of the neural mechanisms underlying these two outcomes. However, interpreting the age-related changes and differences in brain structure, activation and functional connectivity that this research reveals is an ongoing challenge. Ambiguous terminology is a major source of difficulty in this venture. Three terms in particular — compensation, maintenance and reserve — have been used in a number of different ways, and researchers continue to disagree about the kinds of evidence or patterns of results that are required to interpret findings related to these concepts. As such inconsistencies can impede progress in both theoretical and empirical research, here, we aim to clarify and propose consensual definitions of these terms. Age-related changes in cognitive ability are the focus of a growing field of research. Cabeza, Rajah and colleagues aim to promote clarity in the field by agreeing upon consensual definitions for three widely discussed concepts: maintenance, compensation and reserve.